PLOT, CHARACTERIZATION, SETTING, THEME, MESSAGE, AS WELL AS THE VALUE OF CHARACTER EDUCATION IN SHORT STORIES ON A COLLECTION OF SHORT STORIES “SEPOTONG HATI YANG BARU” BY TERE - Sari, Purwanti; Adhani, Agnes (Educatio Vitae, 2018)
This research aims to show and explain: (1) plot, (2) characterization, (3) setting, (4) theme, (5) message, as well as (6) the value of character education in short stories on a collection of short stories “Sepotong Hati yang Baru” by TereLiye. Moreover, this research is descriptive-qualitative research in which data collection was collected from collections of descriptive paragraphs in which aspects that were examined. The findings shown that there were 6 aspects in this research to investigate. The first one is plot, here plot has split into two types of plot: progressive and regressive. Second one is characterization. Here, the characterization has also split up into the main character and additional character. Third, setting, it includes three aspects. They are the setting of time, the setting of place and the social setting. Fourth is theme, there are several major themes; misinterpreted, wife’s sacrifice to husband, the sacrifice of feelings, sacrifice for love, the sacrifice of a woman to her heart’s idol, lack of confidence, family without a foundation of trust, sacrifice to fight for love. Furthermore, other than major theme there is also minor theme such as the sincerity of the heart for the sake of a friend, the loyalty of the wife to the husband, the betrayal of the lover, the loyalty of the lover that she/he want to separate, loyalty to self-sacrifice, sincere companionship, the husband's regrets to his wife and misconceptions about the marriage. Fifth, in this research, the message delivered is to not to be too prejudiced against something, keep promises, do not betray, if we love someone then we have to fight, show how much that love and that compassion, always grateful, trust each other in building a household, and the last but not least is to tell us that we do not regret everything that has happen. The last aspect that discussed in this research was the value of character education in which it includes independence, love peace, discipline, responsibility, hard work, and honesty. Keywords: Plot, Characterization, Theme, Message, and the Value of Character Education.